Identification of different lithofacies laminations in oil shale and their mechanical properties - Cheng, Shizhong; Sheng, Mao; Deng, Chao (Frontiers in Energy Research, 2024)
Lamination can greatly enhance the anisotropy and heterogeneity of shale and plays a significant role in influencing hydraulic fracturing. The structure and mechanical difference of different lithofacies lamination are the basis to reveal the fracture propagation mechanism. In this paper, research focused on three continental oil shale with different lithofacies in Qikou sag, Bohai Bay basin, including Quartz-Feldspar dominated shale, Carbonate dominated shale and mixed-mineral shale. Scanning electron microscopy and mineral analysis are used to identify quartz-feldspar lamination and mixture lamination in Quartz-Feldspar dominated shales, as well as carbonate lamination and mixture lamination in Carbonate dominated shales. The distinct laminations with different characteristics were precisely located using FIB, which served as the guiding tool for the indentation experiment. The micromechanical properties of laminations with different lithofacies in oil shale samples are examined using the nanoindentation technique, highlighting their distinct differences. The findings demonstrate that the micromechanical properties of quartz-feldspar lamination in Quartz-Feldspar dominated shales exhibit superior strength, while the mechanical difference between laminations in Quartz-Feldspar dominated shales are significantly larger. The quartz-feldspar lamination exhibits the highest resistance when subjected to indentation force. The mechanical properties of mixture lamination in Quartz-Feldspar dominated shales and Carbonate dominated shales are comparable due to their similar mineral composition. Moreover, in conjunction with macroscopic rock mechanics experiments, it has been verified that the lamination structure facilitates the initiation and propagation of macroscopic fractures under stress loading.